Application of Passenger and Vehicle Departure Services to the Ticketing System Environment at Ketapang Ferry Port, Banyuwangi Regency, East Java Province - Yohan Wibisono; Budi Mantoro; Carolina Farah Diba (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2021)
The Ketapang ferry port is a commercial ferry port that has implemented